การพัฒนาการจัดการเรียนแบบผสมผสาน เรื่อง ประโยคเพื่อการสื่อสาร สำหรับนักเรียนระดับชั้นประถมศึกษาปีที่ 4 - preecharat, pitchaya (วารสารวิจัยและนวัตกรรมท้องถิ่น, 2022)
This research is research and development. The objectives of this study are 1) To develop online lessons together with the blended learning to be effective according to the criteria E1/E2 = 80/80. 2) To compare scores from pre-test and post-test with online lessons together with blended learning. 3) To study the students’ satisfaction with the online lessons together with the blended learning. The sample used in this study was primary 4 students in the second semester of the academic year 2021 at Ban Nong Tako School, Ban Suan Subdistrict, Mueang Chon Buri District, Chonburi Province, who studied the Thai language by using the school as a random unit for a total of 32 students by clustersampling. The instruments of this study are 1) Online lessons 2) Communicative sentence quiz 3) Satisfaction questionnaire 4) Communication sentence exercises The results of this study were as follows: 1) The results of the development of online lessons together with the blended learning management on communicative sentences for primary 4 students who created the efficiency according to the criteria, E1 was equal to 80.21 and E2 was equal to 81.88 which meets the specified criteria. 2) Comparison of scores from pre-test and post-test, it was found that online lessons together with blended learning students developed statistically significantly higher learning achievements after school than before at the .01 level. 3) The results of the study of students’ satisfaction with online lessons together with blended learning management, it was found that the mean was 4.70 with the highest level.